Characterization and Parametric Optimization of EN-10149-2 Steel Welded Joints Made by MIG Welding - Kedir Beyene Behredin; Perumalla Janaki Ramulu; Beri Habtamu; Negash Besufekad; Negash Tesfaye (Advances in Materials Science and Engineering)
Advanced high strength steels (AHSS) are multiphase steels that contain various concentrations of ferrite, bainite, martensite, and retained austenite phases. The unique physical characteristics of AHSS present some challenges to welding and bonding processes. AHSS have tendency to change microstructure and mechanical properties by any welding process like other steels. Based on the significant applications in various industries, the experimental works are carried out on one of AHSS materials, EN-10149-2 S700MC, with thickness of 2 mm steel sheet metal by MIG welding process parameters such as current, voltage, and welding speed. For all combinations of process parameters, the butt joints are fabricated. The butt joints are inspected through different nondestructive testing for defects detection. All the defect-free joints are characterized through microstructure (at different zones of joint), hardness, and tensile tests. From the obtained mechanical test results, the process parameters are optimized through design of experiment techniques (DoE). The analysis from DoE method is used to identify which parameter is the most significant among all parameters. Confirmatory test is also done by taking the optimal parameters and the result shows that the improvement of the response variables is acceptable and also shows that the method that is used for optimization was valid.